Informal labor markets in times of pandemic: Evidence for Latin America and policy options - Gustavo Leyva; Carlos Urrutia (Banco de México, 2021)
We document the evolution of labor markets of five Latin American countries during the COVID-19 pandemic, with emphasis on informal employment. We show, for most countries, a slump in aggregate employment, mirrored by a fall in labor participation, and a decline in the informality rate. The latter is unprecedented since informality used to cushion the decline in overall employment in previous recessions. Using a business cycle model with a rich labor market structure, we recover the shocks that rationalize the pandemic recession, showing that labor supply shocks and productivity shocks to the informal sector are essential to account for the employment and output loss and for the decline in the informality rate.
Keywords: E24; E32; F44; J65; 330; COVID-19; labor markets; informality; structural model; Brazil; Chile; Colombia; Mexico; Peru